2017
DOI: 10.1007/s10695-017-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine cells producing peptide hormones in the intestine of Nile tilapia: distribution and effects of feeding and fasting on the cell density

Abstract: Endocrine cells (ECs) act as a luminal surveillance system responding to either the presence or absence of food in the gut through the secretion of peptide hormones. The aim of this study was to analyze the effects of feeding and fasting on the EC peptide-specific distribution along the intestine of Nile tilapia. We assessed the density of ECs producing gastrin (GAS), cholecystokinin-8 (CCK-8), neuropeptide Y (NPY), and calcitonin gene-related peptide (CGRP) in nine segments of the intestine using immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…However, it was observed that fish fed with the lower protein level (T1) presented low density of CCK‐IR cells. Similar to our results, fasted Nile tilapia ( Oreochromis niloticus ) presented lower density of CCK‐8 + cells compared to fed ones (Pereira et al., ) and high concentrations of fish meal in the diet have a more potent effect on the stimulation of CCK synthesis and digestive enzymes secretion than other protein sources in yellowtail ( Seriola quinqueradiata ) Furutani, Masumoto and Fukada (). This demonstrates that the source or dietary protein level can positively influence CCK synthesis and promote digestive activities such as pancreatic activity, fluid secretion and intestinal motility (Gribble, ; Murashita et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…However, it was observed that fish fed with the lower protein level (T1) presented low density of CCK‐IR cells. Similar to our results, fasted Nile tilapia ( Oreochromis niloticus ) presented lower density of CCK‐8 + cells compared to fed ones (Pereira et al., ) and high concentrations of fish meal in the diet have a more potent effect on the stimulation of CCK synthesis and digestive enzymes secretion than other protein sources in yellowtail ( Seriola quinqueradiata ) Furutani, Masumoto and Fukada (). This demonstrates that the source or dietary protein level can positively influence CCK synthesis and promote digestive activities such as pancreatic activity, fluid secretion and intestinal motility (Gribble, ; Murashita et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Together our current results and previous (Pereira et al, , ) highlight the restricted distribution of NPY in the first midgut segments, regardless feeding habits, which might play a role as the main signaling area in the intestine to hypothalamic center that modulates food intake.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike Tambaqui but similar to hybrid catfish, the EC CCK in O . niloticus (Pereira et al, ) and gobie, C . gulosus (Hur et al, ), were mainly concentrated in the midgut segment close to the stomach (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations